Marine plastic pollution in the polar south: responses from Antarctic Treaty System - Mengzhu Zhang; Marcus Haward; Jeffrey McGee (2020)
Marine plastic pollution is increasing prominence in current discussions on the governance of the world’s oceans. The Southern Ocean is geographically remote but is still significantly impacted by plastic pollution. Plastic pollution in the Southern Ocean can derive from a variety of sources, including waste from research stations and fishing operations within the Treaty Area and, through transport by ocean currents and wind-generated water movements, from outside the Treaty Area. While there is a growing academic literature on marine plastic pollution in Antarctic, there is less attention to date on the response of the Antarctic Treaty System (ATS) to this issue. This paper analyses how the ATS has engaged with the issue of plastic waste in general, and marine plastic pollution more particularly, from the entry into force of the Protocol on Environmental Protection to the Antarctic Treaty in 1998–2019. Our results indicate that from 2017 the ATS has shown increased attention towards addressing locally sourced marine plastic pollution. A significant problem, however, remains with the respect to marine plastic pollution originating from outside Antarctic Treaty Area that requires a governance response from outside the ATS.